The in vitro assessment of the degree of monomer conversion, biaxial flexural strength, and mineral precipitation on demineralised dentine of novel resin composite containing monocalcium phosphate monohydrate and polylysine - Munchuporn Pariwatanasak; Saowapa Chadarat; Wisitsin Potiprapanpong; Sukanya Kyopun; Anne M. Young; Piyaphong Panpisut (Biomaterial Investigations in Dentistry)
Objective: The development of ion-releasing resin composites is expected to reduce the risk of secondary caries. This study compared the degree of monomer conversion, biaxial flexural strength/modulus, elemental release, and remineralisation potential of a novel ion-releasing dental composite (Renewal MI) containing monocalcium phosphate monohydrate and polylysine.